Perioperative aspiration risk mitigation in a patient with type II achalasia undergoing laparoscopic Heller’s myotomy: A case report. - Vanessa Anza Mukhuba; Claudia Currie Meg; Mogane Palesa N (Student's Journal of Health Research Africa, 2026)
Background Achalasia is a rare oesophageal motility disorder characterised by impaired lower oesophageal sphincter relaxation and absent peristalsis. Progressive oesophageal dilatation results in retained food and secretions despite prolonged fasting, placing patients at high risk of regurgitation and pulmonary aspiration during general anaesthesia. There are no validated perioperative aspiration risk guidelines specific to achalasia. This report aims to describe the perioperative anaesthetic management and aspiration risk mitigation strategies employed in a patient with type II achalasia undergoing a Heller’s myotomy. Case presentation This report describes the anaesthetic management of a 20-year-old male with type II achalasia undergoing laparoscopic Heller myotomy. Despite prolonged fasting of 15 hours for solids and 12 hours for clear fluids, pre-induction nasogastric decompression yielded approximately 800 mL of particulate oesophageal material. Anaesthetic management included head-up positioning, rapid sequence induction with cricoid pressure, continuous nasogastric suctioning, and the use of the suction-assisted laryngoscopy and airway decontamination (SALAD) technique. Endotracheal intubation was successful on the first attempt without regurgitation. Surgery and recovery were uneventful. Take-away lessons Patients with achalasia should be considered high aspiration risk regardless of fasting duration. Prolonged fasting alone may not eliminate retained oesophageal contents. Individualised perioperative planning incorporating dietary modification, oesophageal decompression, protected airway management, and cautious extubation may reduce aspiration risk. Further prospective research is needed to establish evidence-based perioperative management protocols for achalasia.